Planning landscape dimensions, elements, typologies - Zimmermann, Astrid (Birkhäuser, 2015)
Planning Landscape is a well-conceived tool for the planner, which focuses on the two main aspects of ""elements"" and ""typologies."" The planner can flexibly shift between these two according to the specific criterion. The publication presents all information relevant to the planning in a detailed, clear, and cohesive manner.